THE DIG - Sutton, Laurie S.; Nathaniel, James; Colich, Abby (North Mankato, Minnesota : Stone Arch Books, a Capstone Imprint, 2018)
When an archaeologist disappears during a dig on the planet Niburi 3, a world once devastated by a swarm of meteor strikes, Bug Team Alpha are called in to use their DNA-enhanced buglike physical features to investigate--and they find that the original inhabitants were also masters of genetic transformation and left plans for the resurrection of their species.
Keywords: Children's stories, English; English fiction